Respuesta :

CPED

Answer:

part 6: -4x^3(2x^2 - 9x^2)

        =  -4x^3(-7x^2)

       = -4*-7 (x^3+2)

       = 28 x^5

part 7: 5t^-2* 2t^-5

         = 5* 2 (t^-2-5)

         = 10 t^-7

part 8: (3x)^4

        = 3*3*3 x^4+4+4

       = 27 x^12

part 9: (6m^4)^2

        = 6*6 m^4+4

        = 36 m^8

part 10: (x^2)^5 (x^3)^-2

          = x^2+2+2+2+2 * 1/x ^3+3

          = x^10/x^6

         = x^10-6

         = x^4

part 11: (3b^-2)^2 * (a^2*b^4)^3

         = ((3*3)/b^-2-2) * a^2+2+2 * b^4+4+4

         = 9/b^-4 * a^6/b^12

         = 9 a^6 b^12-4

         = 9 a^6 b^8

part 12: (2a^2b^5)^-4* (b^-2a^8)^6

        = (1/2*2*2*2 a^2+2+2+2 2*2*2*2 b^5+5+5+5) (1/b^2+2+2+2+2+2 * a^8+8+8+8+8+8)

      = (1/256 a^8 b^20)(1/b^12 * a^48)

     = (1/256 a^48-8 b^-12-20)

     = 1/256 a^40 b^-32

Part 13: 10^9/10^3

      = 10 ^ 9-3

     = 10 ^ 6

    = 1,000,000

Part 14: 4m^10/2m^8

     = 4/2 m^10 - 8

     = 2 m^2

Part 15: y^3z^10/y^5z^9

     =  y^3-5 z^10-9

    = y^-2 z

    = z/y^2

Part 16: a^8b^6c^7/a^4b^10c^3

        = a^8-4 b^6-10 c^7-3

        = a^4 b^-4 c^4

         =a^4 c^4/ b^4

Part 17: d^2 e^3 f^5/e^6 f^7 g^9

        = d^2 e^3-6 f^5-7 g^-9

        = d^2 e^-3 f^-2 g^-9

        = d^2/e^3 f^2 g^9

Part 18: m^-3/3m^-6

       = 1/3 (m ^ -3-6)

      = 1/3 m^ -9

     

i hope it will help you!